Correspondence with George Cheyne and Thomas Edwards - Richardson, Samuel 1689-1761 (2013)
Samuel Richardson (1689-1761), among the most important and influential English novelists, was also a prolific letter writer. Beyond its extraordinary range, his correspondence holds special interest as that of a practising epistolary novelist, who thought long and hard about the letter as a form. The Cambridge Edition of the Correspondence of Samuel Richardson is the first complete edition of his letters. The present volume contains his correspondences with Dr George Cheyne and Thomas Edwards, linked not only by their pronounced medical content but also by their generally unguarded character. An early admirer of Richardson's Pamela (1740-41), Cheyne elicits some of the novelist's most significant statements concerning his own literary practice and tastes. Edwards, an astute literary critic as well as notable sonneteer, draws Richardson into expressing some remarkable insights as a close reader of poetry and prose
Title from publisher's bibliographic system (viewed on 30 Jun 2022)
Keywords: Richardson, Samuel / 1689-1761 / Correspondence; Cheyne, George / 1671 or 1672-1743 / Correspondence; Edwards, Thomas / 1699-1757 / Correspondence; Edwards, Thomas -- 1699-1757; Cheyne, George -- 1671-1743; Richardson, Samuel -- 1689-1761; Novelists, English / 18th century / Correspondence; Briefsammlung